Localization of small heat shock proteins to the higher plant endomembrane system. - Helm, K W (1993)
Three related gene families of low-molecular-weight (LMW) heat shock proteins (HSPs) have been characterized in plants. We describe a fourth LMW HSP family, represented by PsHSP22.7 from Pisum sativum and GmHSP22.0 from Glycine max, and demonstrate that this family of proteins is endomembrane localized. PsHSP22.7 and GmHSP22.0 are 76.7% identical at the amino acid level. Both proteins have amino-terminal signal peptides and carboxyl-terminal sequences characteristic of endoplasmic reticulum (ER) retention signals. The two proteins closely resemble class I cytoplasmic LMW HSPs, suggesting that they evolved from the cytoplasmic proteins through the addition of the signal peptide and ER retention motif. The endomembrane localization of these proteins was confirmed by cell fractionation. The polypeptide product of PsHSP22.7 mRNA was processed to a smaller-M(r) form by canine pancreatic microsomes; in vivo, GmHSP22.0 polysomal mRNA was found to be predominantly membrane bound. In vitro-processed PsHSP22.7 corresponded in mass and pI to one of two proteins detected in ER fractions from heat-stressed plants by using anti-PsHSP22.7 antibodies. Like other LMW HSPs, PsHSP22.7 was observed in higher-molecular-weight structures with apparent masses of between 80 and 240 kDa. The results reported here indicate that members of this new class of LMW HSPs are most likely resident ER proteins and may be similar in function to related LMW HSPs in the cytoplasm. Along with the HSP90 and HSP70 classes of HSPs, this is the third category of HSPs localized to the ER.